Development of maritime school management as a center of excellent in supporting the learning process - Benny Hartanto; Ningrum Astriawati; Waris Wibowo; Prasetya Sigit Santosa; Handoyo Widyanto (Universitas Muhammadiyah Malang, 2023)
Improving the quality of Human Resources in the marine sector through the development of Vocational High Schools in the Maritime Sector still faces challenges. Link and match with industry have not happened thoroughly other than that educators are not adequate. Vocational High School teachers have not met the needs, so it is necessary to develop the management of Vocational High Schools in the maritime sector. The purpose of this Community Service activity is to conduct training to develop maritime school management to make vocational high schools in the maritime field a Center of Excellence (CoE) in Supporting the Learning Process. The method used in this service activity is training carried out with three kinds, namely: lecture method, discussion and question and answer method as well as an evaluation method. The results of the service show that with this training, the CoE of vocational education vocational schools that are increasingly relevant to the demands of community needs that are constantly changing according to the development of the business/industry world and can support the learning process regularly and continuously. The results of the training evaluation showed the enthusiasm and positive motivation of the trainees which was marked by the value of the evaluation results of the implementation of the training obtained an average score of excellent criteria of 79.33% and a good of 20.67%. After the training, it is hoped that training participants can hone their skills in developing maritime school management.